Teknoloji, işsizlik ve iş hayatında yeni kavramlar - Pehlivanoğlu, M. Çağrı (Hiperyayın, 2023)
Teknolojik gelişmeler birçok sektörde üretim yöntemlerini kökten değişime uğratmaktadır. Özellikle yapay zekâ teknolojisindeki ilerlemelerin çalışanların iş hayatında benzersiz farklılıklara neden olması beklenmektedir. Değişimin belki de en çarpıcı sonucu birçok toplumda yüksek düzeyde iş kaybı yaratacak olmasıdır. İşsizlik bireyler üzerinde olumsuz pek çok sorunu meydana getirmekte kapasitesine sahip olmakla birlikte dünya genelinde başka ekonomik sorunları da tetikleyecektir. Teknoloji kaynaklı olarak yaygınlaşması öngörülen teknolojik işsizlik sorunu, tarihsel geçmişi olan bir kavram olup geçmişten günümüze çalışanların zihninde iş ile ilgili kaygıya neden olmaktadır. Alan yazında yapılan güncel araştırmalar çalışanlarda teknolojik işsizlik kaygısının var olduğunu kanıtlamıştır. Bu bölümün amacı, gelecekte artış gösterecek olan teknoloji kaynaklı işsizlik sorununu değerlendirmektir. Yaşanacak değişimin, insan emeğine olan ihtiyacı dramatik bir şekilde azaltacağı öngörülmektedir.

Technological development are radically changing production methods in many industries. Advances in artificial intelligence technology are expected to create unique differences in the working lives of employees. Perhaps the most striking consequence of this change will be the high levels of job loss in many societies. While unemployment has the capacity to create many negative problems for individuals, it will also trigger other economic problems around the world. Technological unemployment which is predicted to be widespread due to future technologies, is a concept with a historical background and has caused anxiety about work in the minds of workers from the past to the present. Recent studies in the literature have proven that technological unemployment anxiety exists among employees. The aim of this chapter is to evaluate the problem of technological unemployment that will increase in the future. It is predicted that this change will dramatically reduce the need for human labor.
New concepts in technology, unemployment and business life
Keywords: Teknoloji; İşsizlik; Teknolojik işsizlik; Teknolojik işsizlik kaygısı; Technology; Unemployment; Technological unemployment; Technological unemployment anxiety